NILAI TUKAR RUPIAH TERHADAP DOLLAR AMERIKA PASCA KRISIS KEUANGAN: INDIKATOR - INDIKATOR YANG MEMPENGARUHI RUPIAH - FEBRIANUR FEBRIANUR (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2018)
This study aims to identify the most dominant indicators affecting the exchange rate of IDR / USD. The method used in this research is vector autoregressive analysis. In this study the data collected is time series form. The result concludes that inflation, SBI rates, and economic growth except for exports and imports have been shown to affect the IDR / USD exchange rate. In addition, the study also concluded that the SBI rate is the most dominant indicator affecting the exchange rate of IDR / USD.Keyword: Exchange Rate IDR/USD, Macroeconomics, VAR Model